Porosity-Zoned Porous-Transport Layer for Proton-Exchange Membrane Water Electrolysis by High-Velocity Flame Spraying - Bobzin, Kirsten; Finger, Selina; Zhao, Lidong; Heinemann, Hendrik; Olesch, Elisa; Radermacher, Katja; Pechmann, Sabrina; Possart, Dennis; Christiansen, Silke H.; Hoffmeister, Darius; Fritsch, Birk; Thiele, Simon; et al. (Advanced Engineering Materials, 2025)
The porous-transport layer (PTL) is a crucial component in proton-exchange membrane water electrolyzers (PEMWE) enabling water and gas transport as well as electrically contacting the catalyst layer (CL). To reduce the overall costs of PTLs, a fabrication method by high-velocity oxy-fuel (HVOF) spraying is introduced. Free-standing PTLs are obtained via the application of a titanium coating onto a substrate and its subsequent separation and thermal treatment. The obtained PTLs feature two sides of different roughness and porosity as analyzed and visualized by X-ray microscopy. This way, the side with decreased porosity (21%) is intended to function as a microporous layer, improving the contact with the CL. The presented fabrication process promises decreased costs compared to vacuum plasma spraying, a simplified, chemical-free mechanical separation of the PTL from the substrate, and a high scale-up suitability. In the results, it is demonstrated that HVOF can produce titanium PTLs with low oxygen content. Additionally, PEMWE single-cell tests demonstrate that the sprayed PTLs perform on par with a commercially available PTL material.
CRIS-Team Scopus Importer:2025-01-31
Keywords: asymmetric porosity; high-velocity oxy-fuel spraying; microporous layer; porous structure; single-cell test; thermal spraying; titanium particles